Delivering wow : how dentists can build a fascinating brand and achieve more while working less - Holmes, Anissa (Morgan James Publishing, 2019)
Delivering WOW is a blueprint for running and growing a dental practice. Dr. Anissa Holmes was sick of working too much and earning too little, so she decided to do something about it. After years of learning and experimentation, she developed a simple, high-impact process to run and grow a dental practice that turned her office into a high-profit practice with over 50,000 raving Facebook fans and a reliable team she can trust to handle anything that comes their way. With this newly-updated and expanded version of a book that helped thousands of dentists build more profitable and enjoyable dental practices, Dr. Holmes walks dentists through building a winning team, maximizing profitability, and reliably growing patient numbers without having to waste time and money on expensive and ineffective advertising methods.